2007
DOI: 10.1016/s1015-9584(09)60136-6
|View full text |Cite
|
Sign up to set email alerts
|

Seminoma in a Male Phenotype 46XX True Hermaphrodite

Abstract: Although true hermaphrodite is uncommon, it has been reported in more than 400 individuals. Tumours arising in the gonads of true hermaphrodite is a very rare finding and only very few cases have been reported in the literature. We report a case of a 35-year-old phenotype man with bilateral undescended testis with lump hypogastrium. On examination, he had an ovotestis on one side and pure seminoma arising in testis on the other side. The seminoma arising in the left undescended testis was successfully treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…(). Interestingly, there have been four recent reports of seminoma arising in ovotestes in coincidence with current trends to preserve the testicular component in cases of male sex assignment (Nichter, ; Malavaud et al ., ; Malik et al ., ; Hua et al ., ). The problem is further complicated because in largest series of OT‐DSD the identification of testicular CIS has not even been attempted.…”
Section: Discussionmentioning
confidence: 96%
“…(). Interestingly, there have been four recent reports of seminoma arising in ovotestes in coincidence with current trends to preserve the testicular component in cases of male sex assignment (Nichter, ; Malavaud et al ., ; Malik et al ., ; Hua et al ., ). The problem is further complicated because in largest series of OT‐DSD the identification of testicular CIS has not even been attempted.…”
Section: Discussionmentioning
confidence: 96%
“…Recent evidence indicated that SRY is permissive but not mandatory for male development. [6] Other causes of XX OT-DSD include mutations in NR5A1 , aberrant expression of SOX3 , duplication of SOX9 , and mutations in RSPO1 and WNT4 . [ 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…To date, less than ten cases of tumors arising in the gonads of individuals with 46,XX OT-DSD have been reported. [ 5 6 7 8 9 10 ] As shown in Table 1 , all adults were classified as male. Five out of 7 patients presented with seminoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a true hermaphrodite is uncommon, it has been reported in more than 400 individuals [5]. It is generally known that almost all hermaphrodites are infertile, however, German et al [6] observed spermatogenesis in an hermaphrodite.…”
Section: Introductionmentioning
confidence: 99%